Multi-Frame Compressed Video Quality Enhancement by Spatio-Temporal Information Balance - Wang, Zeyang; Ye, Mao; Li, Shuai; Li, Xue (IEEE signal processing letters, 2023)
In recent years, the performance of multi-frame quality enhancement algorithms for compressed videos has been greatly improved compared with single-frame based algorithms. However, the existing methods mainly focus on mining the temporal information of multiple frames. The large number of reference frames reduces the exploration of spatial information, although the existing single-frame based algorithms for enhancement, denoising, and super-resolution demonstrate the significance of the spatial information. To address this problem, we propose a plug-and-play module called Spatio-temporal Information Balance (STIB) to adaptively balance the spatial and temporal information. In our method, we use a feature extractor to exploit richer spatial information, and use a refinement module to refine the aligned temporal information, to be more conducive to the fusion of spatio-temporal information. Finally, we use the deformable convolution based re-alignment module to do alignment and fusion in feature space for balancing the spatio-temporal information. Experiments show that our module can significantly improve the performance of the existing multi-frame based enhancement algorithms.